(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Wireless body area network (WBAN) is an emerging technology which is getting a lot of attention these days due to its application in medical field and health monitoring system. In this technology by using different bio-sensors which could be implanted or worn by patient, he/she get his/her health conditions at regular intervals. Wireless connectivity makes it more popular because of its patient could use it in his daily life activities also. There are various fields in WBAN where a lot of development could be made, as this field is still in its developing stages. Efficient energy utilisation techniques have been explained. Routing metrices which consists of residual energy, delay, packet collision, network lifetime, complexity, network traffic etc. is also an interesting area where we will be working to develop intelligent routing metrices for wireless body Area Network (WBAN).Fuzzy Logic(FL) is a powerful tool used to develop solution of various problems today which maps the crisps inputs to give corresponding outputs. Momdani Fuzzy Inference System (FIS) provides the atmosphere needed for Fuzzy Logics where depending on degree of membership functions maps the variables and a surface is generated with respect to various factors in routing metrics. In this paper we had reviewed its basic aspects like its constituents, layered architecture and Issues as well as requirements of WBAN with Fuzzy Inference System (FIS). Keywords: Wireless Body Area Network, WBAN, Routing Metrices, Layered Architecture, Fuzzy Logic, Energy efficiency, Fuzzy Inference System (FIS).